A DESCRIPTIVE STUDY ON TEACHING PRONOUN TO THE FIFTH YEAR STUDENT AT SD N 3 JENENGAN, BOYOLALI IN 2010/2011 ACADEMIC YEAR - Wulandari, Wulandari (2011)
This research paper is intended to describe (1) curriculum used by the teacher in teaching pronouns, (2) the method used by the teacher in teaching pronouns, (3) the media used by the teacher in teaching pronouns, and (4) system of evaluation used by the teacher in teaching pronouns. This study is a qualitative research. In collecting the data, the writer uses observation, interview, and document. The technique to analyzing the data involves (1) describing the process of teaching pronouns, (2) discussing the finding of the research, and (3) drawing conclusion, and proposing suggestion. The results of the study show that (1) curriculum used by the teacher in teaching pronoun process is School Level-based Curriculum, (2) the method used by the teacher in teaching pronoun is Grammar Translation Method (GTM), (3) the media used by the teacher in teaching learning pronouns are board, board marker and concrete objects in class surrounding and the classroom, and (4) the evaluation system used by the teacher consist, of 3 kinds of test: periodical test, mid test and final test. Besides, the teacher takes the evaluation from assignment, homework, and student activity in the classroom.